Tribological compatibility analysis of conventional lubricant additives with palm trimethylolpropane ester (TMP) and tetrahedral amorphous diamond-like carbon coating (ta-C) - Zahid, Rehan; Mufti, Riaz Ahmad; Gulzar, Mubashir; Masjuki, Haji Hassan; Alabdulkarem, Abdullah; Varman, Mahendra; Kalam, Md. Abul; Zulkifli, Nurin Wahidah Mohd; Yunus, Robiah (SAGE Publications (UK and US), 2018)
Modern industrial applications involve rigorous operating conditions due to which lubricant either slips out of the contact or its thin layer resides between the interacting surfaces. Deposition of diamond-like carbon coatings and using lubricants capable of physically adsorbing on the interacting surfaces can significantly improve tribological performance. In this study, tribological compatibility of glycerol mono-oleate, molybdenum dithiocarbamate and zinc dialkyldithiophosphate with palm trimethylolpropane ester and tetrahedral amorphous diamond-like carbon coating has been investigated using universal wear testing machine. For comparison, additive-free and formulated versions of polyalphaolefin were used. Moreover, spectroscopic techniques were used to investigate mechanisms responsible for a particular tribological behavior. Among base oils, trimethylolpropane ester proved to be more effective in enhancing friction performance and mitigating wear of contacts when one of the interacting surfaces was ferrous-based. Self-mated tetrahedral amorphous diamond-like carbon coating surfaces resulted in lowest values of friction and wear coefficient of balls.